NURSEAND SPIRITUALITY - O`rol Abilov (Web of Journals Publishing, 2023)
Spirituality is an incomparable force that calls a person to spiritual purification, spiritual growth, strengthens his inner world, strengthens his will, completes his faith, awakens his conscience, and is the criterion of all his views. The moral characteristics and qualities of medical personnel reflect their cultural and deontological level.